EVALUATION OF ORAL BEHAVIOR IN A GROUP OF PATIENTS WITH SELF-REPORTED SLEEP BRUXISM - Steliana Gabriela Buștiuc; Gheorghe Raftu; Raluca Briceag; Elena Claudia Sin; Mihaela Macrina Manolache; Cristina Nucă; Salim Camer; Aureliana Caraiane (Romanian Journal of Medical and Dental Education)
The first version of the Standardised Tool for the Assessment of Bruxism (STAB) was published in 2024. The oral behaviour checklist (OBC) is included in the STAB and is a self-assessment tool designed to assess the frequency of various oral behaviours during the day or night. Oral behaviours have been clearly identified as a risk factor for the development of painful TMD. The aim of this study was to identify oral behaviors in a group of patients with self-reported sleep bruxism (SB). Material and methods: This is a cross-sectional study which was carried out by administering OBC in a group of patients with self-reported SB in order to assess oral behaviors during the day and night. Results: It was highlighted that the average score obtained by completing the OBC was 20.519±6.970 (standard deviation). Most of the patients – 36.71% obtained scores that fell within the 17-24 range. Conclusions: Most patients presented OBC scores that fell within the range of 17-24, a range that, according to the literature, occurs twice as often in those with TMD. A fairly high percentage was recorded for scores that fell within the range considered to be a risk factor for the occurrence of TMD (25-62). All these findings lead to the strengthening of the idea that intercepting an increased frequency of oral behaviors in patients with SB can lead to the identification of those patients who could develop TMD over time, with the dentist having the role of providing TMD prevention in this context.